Prevalence and transmission dynamics of Escherichia coli ST131 among contacts of infected community and hospitalized patients. (June 2018) - Torres, E.; López-Cerero, L.; Morales, I.; Navarro, M.D.; Rodríguez-Baño, J.; Pascual, A.
Abstract: Objectives: The Escherichia coli O25b-associated ST131 clonal group was recently found to be prevalent in our area as a cause of community-acquired urinary tract infections. We evaluated the transmission dynamics and longitudinal persistence of E. coli O25b-ST131 between patients with nosocomial and community-acquired infections and their contacts. Methods: Prevalence and transmission of O25b/ pab B3/B23 isolates were compared in 38 community clusters, 30 nosocomial clusters and 50 healthy volunteers. Duration of colonization was studied at 1 to 4 months and 6 to 12 months after the first sample. Isolates exhibiting a three-band or less difference by pulsed-field gel electrophoresis were assigned to the same pulsotype. Results: Colonization was found to be more frequent in index cases (31/68, 45.6%) than in contacts (25/118, 21.2%; p 0.0009) or volunteers (1/50, 2%; p 0.0009). Seven (11%) of 64 isolates were extended-spectrum β-lactamase producers. Transmission occurred in 61% (8/13) community clusters and in 12% (1/8) nosocomial clusters. Thirteen (56.5%) of the 23 initial carriers assessed at 1 to 4 months remained colonized. Only 2 (13.3%) of 15 positive patients followed for 6 to 12 months showed prolonged carriage, and none was infected with extended-spectrum β-lactamase producers. Six previously positive individuals acquired a different ST131 pulsotype (5/23 at sample 2 and 1/15 at sample 3), and three previously negative individuals became positive (2/46 at 1–4 months and 1/33 at 6–12 months). Conclusions: Person-to-person transmission or acquisition from a common source of E. coli O25b-associated ST131 is more frequent in the household setting than in the nosocomial setting. The carrier state does not usually last beyond 4 months, with new acquisitions in certain individuals.